TEENAGER’S RESPIRATORY SYSTEM VALUES DYNAMICS - Jakubovskaya, Irina; Makunina, Olga; Bykov, Eugeney; Kraynik, Victor; Kolokoltsev, Mikhail; Romanova, Elena (Revista Inclusiones, 2020)
Features of the formation of the organism at different stages of ontogenesis under the influence of negative environmental factors. Material: Direct measurements and some number of values calculation were carried out using generally accepted methods: chest rise (CR, sm), pulmonary capacity ratio (PC), and also some functional tests: timed inspiratory capacity (Stange’s test) and timed expiratory capacity (Genchi’s test). 58 schoolchildren (30 girls, 28 boys), aged 15-17 took part in the research. External respiration values assessment was carried out by spirometry. When assessing external respiration, pulmonary capacity ratio (PC) was analyzed and functional tests of the respiratory system were carried out during timed inspiratory capacity (Stange’s test) and timed expiratory capacity (Genchi’s test), also chest rise (CR, sm) was measured. Results: The results of the respiratory system research generally indicate compliance with age norms. However, pulmonary capacity ratio (PC) values have honestly significant sex differences. The relatively large boys’ pulmonary capacity ratio values are due to the physiological and metric parameters represented by the chest circumference and its rise (CR, sm).The data obtained expand the scientific image concerning the organism formation peculiarities at different ontogenesis stages under the influence of negative environmental factors. Normal teenagers’ physical development rates are accompanied by acceleration of growing respiratory organs’ deviations and diseases (up to 8,9%)